(3GdLhgQI GdefjaI aj TQM hUjI CHj MfjaIs - (3eKdG MSjf Hf EScfOQ GdMfajs; (3CHh MfjaI , CHh MfjaI,J (B150 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeJhMO HhLhH GdhLhO hGdHbGA jbhd GdYHO GdMbjQ GdabjQ GdeOYh HefdG MSjf Hf EScfOQ GdMfai hHYO aEfi ESJNQJ Gddg JYGdi ai TQM eNJUQ Ydi cJGH GdhUjI GdefShH Edi GdEeGe GdCYXe CHj MfjaI s
(3BNQgG (B:s
(3hGdMeO ddg Ydi GdJeGe hbO hbY GdaQGZ ef JCdja TQM cJGH GdhUjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B36 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B104s
Keywords: (3Gdabg GdESdGejs